TAX PLANNING DAN NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN PERTAMBANGAN DI BEI TAHUN 2016-2018) - Juliati Juliati; Rahmawati (JWM (JURNAL WAWASAN MANAJEMEN), 2022)
Aggressive tax planning has an impact on reducing the amount of taxes that must be paid to the state. Several mining companies in Indonesia are indicated to carry out aggressive tax planning. By using signal theory, companies that carry out tax planning can have an impact on decreasing the value of the company because the company is indicated to have violated tax regulations. This study will examine whether the tax planning by the company has a negative effect on the company. The research design used is quantitative research using hypotheses. The hypothesis proposed is that tax planning has a negative effect on firm value. Hypothesis testing using multiple linear regression. The research sample used is a mining company that went public on the Indonesia Stock Exchange (IDX) in 2016 – 2018. The independent variable is tax planning while the dependent variable is company value, this study also uses control variables, namely profitability and leverage. Measurement of tax planning by using the effective tax rate (ETR) and ETR differential, while the value of the company is measured by using the price to earnings ratio (PER). Profitability control variable is measured using return on assets (ROA) and leverage is measured using debt to equity ratio (DER). The results show that the smaller the ETR, the smaller the PER of the company. The larger the ETR differential, the smaller the PER of the company. The smaller the ETR or the larger the ETR differential indicates that the more aggressive the tax planning is carried out by the company and the greater the tax planning will have an impact on decreasing the value of the company so that the hypothesis in this study is accepted. The conclusion of this study is that tax planning that is carried out aggressively by the company can potentially violate tax regulations applied by a country so that this policy can affect the value of the company to be down.Keywords: tax planning, firm value